MENEMUKAN IMAN DALAM KETIDAKPASTIAN: REFLEKSI TEOLOGIS BERDASARKAN KITAB HABAKUK - Iman Kristina Halawa; Daniel Pesah Purwonugroho; Martha Bela Wowo; Yosafat Gratia Prasetyo (Sekolah Tinggi Teologi Arastamar Bengkulu, 2024)
This paper is organized to find faith in uncertainty through theological reflection based on the book of Habakkuk. Habakkuk is a prophet of God in the Old Testament who experienced a difficult time amid King Jehoiakim's reign. The difficulties of life and injustice that occurred during the time of King Jehoiakim made the prophet Habakkuk constantly pray and put his faith in God. This steadfastness of faith needs to be emulated by believers. The modern age in which believers live often brings various challenges, such as the relativism of absolute truth and identity crisis. As a believer living in modern times, I believe that imitating Habakkuk can be done to achieve faith resilience. By having faith resilience as a result of imitating Habakkuk, believers can get through difficult times through their faith. Believers' faith will be trained amid life's uncertainties. Through descriptive qualitative research methods, the author tries to narrate the discovery of faith amid uncertain conditions through theological reflection based on the book of Habakkuk. The author states that the theological reflection of the book of Habakkuk brings believers to have faith that even amid uncertainty, God still answers prayer.